Bacillus subtilis YdiH Is a Direct Negative Regulator of the cydABCD Operon - Schau, Matthew (American Society for Microbiology, 2004)
During aerobic respiration, Bacillus subtilis utilizes three terminal oxidases, cytochromes aa(3), caa(3), and bd. Cytochrome bd is encoded by the cydABCD operon. We report here the first identification of a regulator for the cydABCD operon, YdiH. While working with ΔresDE mutant strains, we identified colonies which contained suppressor mutations (cmp) which bypassed the requirement for ResD for all phenotypes not associated with cytochrome aa(3) or caa(3). Mapping identified a class of Tn10 insertions which were close to the cmp locus (Tn10-2) and a second class (Tn10-1) which was inserted in cydD, a gene which appears to be essential to the cmp phenotype. Sequencing of the cmp loci from four independent ΔresDE cmp isolates yielded four loss-of-function alleles of ydiH, a gene encoding a protein with homology to AT-rich DNA-binding proteins. Additionally, we determined that cytochrome bd was aberrantly expressed in the ΔresDE cmp background. Together these data led to the hypothesis that YdiH serves as a negative regulator of cydABCD expression, a hypothesis supported by both gel-shift and DNase I footprinting analyses. YdiH protected the cydA promoter region at three 22-bp repeats located in the long 5′ untranslated region (193 bp). Induction of the cydABCD operon in a ΔresDE background showed that expression of the terminal oxidase bd was responsible for the bypass phenotype observed in a ΔresDE cmp strain, indicating that cytochrome bd expression complemented the loss of cytochromes aa(3) and caa(3) in the ΔresDE strain.